2000
DOI: 10.1088/0953-8984/12/39/306
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulation of the effect of temperature and pressure on point defect formation in MgSiO3perovskite and the stability of CaSiO3perovskite

Abstract: We present an atomistic simulation method for calculating the defect formation free energy and defect volume using lattice dynamics. The periodic simulation methods have been extended to allow charged systems with subtraction of defect-defect interactions to be studied routinely. This allows constant pressure minimization to be used rather than the more traditional constant volume method, allowing direct calculation of defect formation volumes and defect free energies or enthalpies rather than lattice energy.W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…␣-PbO 2 to pyrite phase transition. Our results are comparable with previous calculations 17, 32 and experimental 33,34 data for silicates at high pressure.…”
Section: B Migration Enthalpiessupporting
confidence: 93%
“…␣-PbO 2 to pyrite phase transition. Our results are comparable with previous calculations 17, 32 and experimental 33,34 data for silicates at high pressure.…”
Section: B Migration Enthalpiessupporting
confidence: 93%
“…CaSiO 3 perovskite has also instigated several theoretical calculations (Stixrude et al 1996;Chizmeshya et al 1996;Warren et al 1998;Magyari-Kope et al 2002a, b;Akber-Knutson et al 2002;Jung and Oganov 2005;Caracas et al 2005), and is found to be Pnam and I4/mcm at pressures above 14.2 GPa at 0 K. For a review of these calculations, see Jung and Oganov (2005). A variety of physical properties such as high temperature, high pressure properties, in particular elasticity (Adams and Oganov 2006;Li et al 2006), trace element incorporation (Corgne et al 2003), melting behaviour (Wang 1999) and solubility with MgSiO 3 (Kesson et al 1995;Watson et al 2000;Vitos et al 2006) have been investigated using theoretical calculations.…”
Section: Introductionmentioning
confidence: 95%
“…This difference in ionic size was calculated according to a scheme based on bond strengths, coordination number and single crystal measurements. Watson et al (2000) employed an atomistic simulation method based on the Born model of solids in which the individual interactions are defined by interatomic potentials. They calculated the Ca partitioning within the lower mantle through the solution energy of Ca in MgSiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Their work showed that solution energies show a parabolic dependence on ionic radii and in the case of heterovalent substitutions, the solution energy of a trivalent cation was dependent on the nature of the charge compensating species. Watson et al (2000) investigated the defect chemistry of MgSiO 3 perovskite at high pressure and its ability to form solid solutions with CaSiO 3 . At the time, experimental observations gave conflicting results.…”
Section: Applicationsmentioning
confidence: 99%